Corporate Tax Management Strategy as an Effort for Good Corporate Governance - Suharto, Suharto (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
Tax preparation enterprises play a vital role in assisting people and corporations in comprehending and adhering to intricate tax legislation. Nevertheless, due to the escalating competition, tax preparation enterprises must embrace pertinent and groundbreaking marketing tactics in the Internet age. This study aims to examine and evaluate the execution of efficient marketing tactics within the tax preparation industry. This study employs a qualitative methodology utilizing descriptive techniques. The research findings indicate that implementing marketing tactics in the tax preparation industry favors enhancing brand visibility, recruiting new clientele, and fostering business expansion. Employing a blend of online and offline marketing tactics, such as content marketing and a dynamic social media presence, has expanded the reach to a broader demographic. SMART goal setting and KPI measurement facilitate the assessment of marketing initiatives' effectiveness, while data analysis using technologies such as Google Analytics yields valuable insights into customer behavior and market trends. Moreover, the computation of return on investment (ROI) enables firms to allocate expenditures in a resourceful manner, ascertain the most impactful marketing channels, and enhance the long-term viability of growth.